Optimization of Culture Medium Enhances Viable Biomass Production and Biocontrol Efficacy of the Antagonistic Yeast, Candida diversa - Liu, Jia; Li, Guangkun; Sui, Yuan (Frontiers in Microbiology, 2017)
Viable biomass production is a key determinant of suitability of antagonistic yeasts as potential biocontrol agents. This study investigated the effects of three metal ions (magnesium, ferrous, and zinc) on biomass production and viability of the antagonistic yeast, Candida diversa. Using response surface methodology to optimize medium components, a maximum biomass was obtained, when the collective Mg2+, Fe2+ and Zn2+ concentrations were adjusted in a minimal mineral (MM) medium. Compared with the unmodified MM, and three ion-deficient MM media, yeast cells cultured in the three ion-modified MM medium exhibited a lower level of cellular oxidative damage, and a higher level of antioxidant enzyme activity. A biocontrol assay indicated that C. diversa grown in the ion-modified MM exhibited the greatest level of control of gray mold on apple fruit. These results provide new information on culture medium optimization to grow yeast antagonists in order to improve biomass production and biocontrol efficacy.